Penggunaan Smartphone Dalam Memberikan Informasi Kesehatan Reproduksi Remaja - Sari Anggela; Dessie Wanda (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Adolescence is a transition period between childhood and adulthood when physical, cognitive, social and emotional maturity grow rapidly to prepare for being adult men and women. The most common problem for existing adolescence is reproductive health problems. The effective method is needed to convey information about reproductive health to adolescents like using smartphone. Objective: to find out the intervention and benefits of using smartphone for serving adolescent reproductive health information. Methods: literature review using Scopus, Ebsco, Science Direct, and Proquest databases from 2012-2019. Results: 17 articles related to the using of smartphones for serving information about adolescent reproductive health. Conclusion: Information about reproductive health through using smartphone can be effectively in increasing adolescent knowledge, attitudes, motivation, and self-efficacy related to reproductive health and highly motivating adolescents to participate on HIV and STI examinations. Information service using smartphones will be highly recommended for teens get information about health reproduction Keywords: smartphone; health Information; reproduction; adolescent ABSTRAK Latar berlakang: Masa remaja merupakan suatu periode transisi antara masa kanak-kanak dan masa dewasa, merupakan waktu kematangan fisik, kognitif, sosial dan emosional yang cepat untuk mempersiapkan diri menjadi laki-laki dan perempuan dewasa. Permasalahan yang paling sering terjadi pada masa remaja saat ini adalah masalah kesehatan reproduksi. Metode yang tepat diperlukan untuk menyampaikan informasi tentang kesehatan reproduksi kepada remaja salah satunya dengan menggunakan smartphone. Tujuan: untuk mengetahui intervensi dan manfaat smartphone dalam memberikan informasi kesehatan reproduksi remaja. Metode: tinjauan literatur menggunakan database Scopus, Ebsco, Science Direct, dan Proquest dari tahun 2012-2019. Hasil: 17 artikel terkait dengan penggunaan smartphone dalam memberikan informasi kesehatan reproduksi remaja. Kesimpulan: Informasi kesehatan reproduksi melalui smartphone dapat digunakan untuk meningkatkan pengetahuan, sikap, motivasi, serta efikasi diri remaja yang berhubungan dengan kesehatan reproduksi serta dapat memotivasi remaja untuk melakukan pemeriksaan HIV dan IMS. Pemberian informasi melalui smartphone dapat membantu remaja dalam mendapatkan informasi terkait kesehatan reproduksi. Kata kunci: smartphone; informasi kesehatan; reproduksi; remaja